2019
DOI: 10.1074/jbc.rev119.009178
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR: A powerful tool for structural and functional studies of membrane proteins in reconstituted environments

Abstract: Edited by Karen G. Fleming A third of the genes in prokaryotic and eukaryotic genomes encode membrane proteins that are either essential for signal transduction and solute transport or function as scaffold structures. Unlike many of their soluble counterparts, the overall structural and functional organization of membrane proteins is sparingly understood. Recent advances in X-ray crystallography, cryo-EM, and nuclear magnetic resonance (NMR) are closing this gap by enabling an in-depth view of these ever-elusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 147 publications
0
54
0
Order By: Relevance
“…In that study, the authors determined an ensemble of cryoEM structures of yeast TRiC/ CCT at various nucleotide concentrations that included both open and closed states, revealing an unforeseen allosteric network at atomic resolution. Visualizing the cytoplasmic domains of CD3 subunits may require cryoEM analysis of the TCR-CD3 complex in nondetergent systems, such as nanodiscs or amphipols, that may more faithfully reproduce a natural lipid environment (67,71). Finally, none of the conventional structural methods used to study TCR triggering (X-ray crystallography, NMR, and cryoEM) take into account mechanical force, as posited in the mechanosensor model.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the authors determined an ensemble of cryoEM structures of yeast TRiC/ CCT at various nucleotide concentrations that included both open and closed states, revealing an unforeseen allosteric network at atomic resolution. Visualizing the cytoplasmic domains of CD3 subunits may require cryoEM analysis of the TCR-CD3 complex in nondetergent systems, such as nanodiscs or amphipols, that may more faithfully reproduce a natural lipid environment (67,71). Finally, none of the conventional structural methods used to study TCR triggering (X-ray crystallography, NMR, and cryoEM) take into account mechanical force, as posited in the mechanosensor model.…”
Section: Discussionmentioning
confidence: 99%
“…This means that by altering q , the suitability of this system can be adjusted for a range of biophysical techniques. For example, DMPC-DHPC bicelles prepared with q values > 2.3 will align with a magnetic field and can be used in oriented-sample solid-state NMR in order to establish 15 N-labelled amide bond orientations and the TM helix angle of the incorporated proteins relative to the bilayer normal [ 237 , 238 ], whilst q values ≤ 0.7 allow bicelles to be sufficiently small for solution-state NMR to be carried out [ 239 ].…”
Section: Membrane Mimetic Systems For Structural and Functional Stmentioning
confidence: 99%
“…Unfortunately the large size of liposomes even when using SUVs generally precludes their use for solution NMR studies ( Figure 4 ) aiming at a characterisation directly on the intact receptor [ 237 ]. However, waterLOGSY-based NMR spectroscopy has been successfully applied to study the membrane association of the truncated C terminus of the B-type CGRP receptor [ 265 ].…”
Section: Membrane Mimetic Systems For Structural and Functional Stmentioning
confidence: 99%
“…Most recently, its applications have expanded into resolving the cryo-EM structures of alternative complex III in a supercomplex with cytochrome oxidase [79]. In comparison to nanodiscs and detergent systems, an overall smaller molecular weight assembly might offer favorable relaxation advantages for NMR application [80], though no NMR studies of SMALP-reconstituted GPCRs have been reported. An adaptable phospholipid membrane mimetic system was also developed for solution state NMR studies and it has been tested in several proteins, including GPCR [81].…”
Section: Receptor Conformational Resolution Limitation and Solutionsmentioning
confidence: 99%